Tuning Transcription Factor Availability through Acetylation-Mediated Genomic Redistribution - Louphrasitthiphol, Pakavarin; Siddaway, Robert; Loffreda, Alessia; Pogenberg, Vivian; Friedrichsen, Hans; Schepsky, Alexander; Zeng, Zhiqiang; Lu, Min; Strub, Thomas; Freter, Rasmus; Lisle, Richard; Suer, Eda; et al. (Molecular cell, 2020)
It is widely assumed that decreasing transcription factor DNA-binding affinity reduces transcription initiation by diminishing occupancy of sequence-specific regulatory elements. However, in vivo transcription factors find their binding sites while confronted with a large excess of low-affinity degenerate motifs. Here, using the melanoma lineage survival oncogene MITF as a model, we show that low-affinity binding sites act as a competitive reservoir in vivo from which transcription factors are released by mitogen-activated protein kinase (MAPK)-stimulated acetylation to promote increased occupancy of their regulatory elements. Consequently, a low-DNA-binding-affinity acetylation-mimetic MITF mutation supports melanocyte development and drives tumorigenesis, whereas a high-affinity non-acetylatable mutant does not. The results reveal a paradoxical acetylation-mediated molecular clutch that tunes transcription factor availability via genome-wide redistribution and couples BRAF to tumorigenesis. Our results further suggest that p300/CREB-binding protein-mediated transcription factor acetylation may represent a common mechanism to control transcription factor availability.